De mãe em filha: a transmissão da feminilidade - Ribeiro, Marina Ferreira da Rosa (2009)
The main aim of this study was to find grounds and support from the psychoanalytical literature for the existence of specific psychological vicissitudes along the path from baby to girl to woman. The concepts put forward by certain psychoanalysts regarding this very intricate relationship and their effects on the continual challenge of becoming a woman and on the transmission of feminineness were investigated and analyzed. Freud s observations on the inexorable suppression that covers up the primordial relationship between mothers and their daughters were the starting point. Expressions for the nuances of the vestiges of this archaic relationship with mothers were sought; for daughters, their mothers are both the primary and the secondary objects of identification. Mothers eroticize their baby girls, leaving sensual traces for future adult enjoyment of female sexuality. In this relationship of like that engenders like, there is a potential risk of narcissistic entrapment and symbiotic illusion. Hostility between mothers and daughters was taken to be a search for psychological differentiation, which is always present to a greater or lesser extent. The passion between mother and daughter was shown firstly through the myth of Demeter and Persephone. The tragedy of Electra was dealt with as the other face of passion: hate. The conceptual framework surrounding feminineness in psychoanalysis was investigated and linked in, and the origin and development of the following concepts was explained: primary female identification (Paulo de Carvalho Ribeiro), primary homosexuality (Jacqueline Godfrind), primary female position or phase of feminineness (Melanie Klein) and primary maternalism and primary femaleness (Florence Guignard). The film Autumn Sonata by Ingmar Bergman was analyzed, focusing on the unsustainable nostalgia of meeting the mother, which was always dreamed of and never achieved. Continuing the reflections on the film, the male viewpoint and its indissociable dialectic connection with the female viewpoint is demonstrated. This coming together between female and male viewpoints brings to the fore the concept of psychological bisexuality. The different objective rules of mothers and fathers were also discussed. Two clinical constructions were presented: Zoe and Liz. Finally, the preciousness and tanatic , or the strength and vulnerability of the transmission of the feminineness from mothers to daughters were investigated